The relationship between the character of responsibility and academic procrastination in students - Zaimi, Melati; Sukma, Dina (Counseling and Humanities Review, 2023)
Procrastination is a procrastinating behavior in carrying out tasks. Factors causing academic procrastination. If they do not have awareness of the task they have, such as the character of responsibility, students will increasingly procrastinate this behavior. This study aims to analyze: (1) the character of responsibility, (2) students' academic procrastination, and (3) examine the relationship between the character of responsibility and academic procrastination in students and the implications for counseling services. This research method is a quantitative method with a descriptive correlational research type. The study population consisted of 746 students of class X and XI of SMA Negeri 9 Padang with a sample of 260 students selected by Stratified Random Sampling. The instrument used is the "Responsibility Character Instrument and Student Academic Procrastination Instrument" using a Likert model scale. Data were analyzed using descriptive statistical techniques and Pearson Product Moment correlation techniques. The research findings show that: (1) support for the character of responsibility is in the low category, (2) academic procrastination is in the high category, (3) and there is a significant negative relationship between peer social support and students' emotional maturity with a correlation coefficient of -0.562 and a significance level of 0.000. The implications for Guidance and Counseling will be discussed.